Influence of Normal Loads and Sliding Velocities on Friction Properties of Engineering Plastics Sliding against Rough Counterfaces - Nuruzzaman, D. M.; Chowdhury, M. A.; Rahaman, M. L.; A. N., Oumer (IOP Publishing Ltd., UK, 2016)
Friction properties of plastic materials are very important under dry sliding contact conditions for bearing applications. In the present research, friction properties of engineering plastics such as polytetrafluoroethylene (PTFE) and nylon are investigated under dry sliding contact conditions. In the experiments, PTFE and nylon slide against different rough counterfaces such as mild steel and stainless steel 316 (SS 316). Frictional tests are carried out at low loads 5, 7.5 and 10 N, low sliding velocities 0.5, 0.75 and 1 m/s and relative humidity 70%. The obtained results reveal that friction coefficient of PTFE increases with the increase in normal loads and sliding velocities within the observed range. On the other hand, frictional values of nylon decrease with the increase in normal loads and sliding velocities. It is observed that in general, these polymers show higher frictional values when sliding against SS 316 rather than mild steel. During running-in process, friction coefficient of PTFE and nylon steadily increases with the increase in rubbing time and after certain duration of rubbing, it remains at steady level. At identical operating conditions, the frictional values are significantly different depending on normal load, sliding velocity and material pair. It is also observed that in general, the influence of normal load on the friction properties of PTFE and nylon is greater than that of sliding velocity.